The effects of using corrugated booster reflectors to improve the performance of a novel solar collector to apply in cooling PV cells-Navigating performance using ANN - Abu-Hamdeh, Nidal H.; Öztop, Hakan Fehmi; Alnefaie, Khalid A.; Ahmadian, Ali; Baleanu, Dumitru (Springer, 2021)
In this study, turbulent flow and heat transfer of water in a solar collector equipped with corrugated booster reflectors to apply in cooling photovoltaic cells (PV) are investigated. 3D simulation is done using by the control volume method and SIMPLEC algorithm. The optimization was carried out by comparison of different parameters to reach the optimal situation with the maximum efficiencies of energy and exergy. It is established that in the case of corrugated booster reflectors, the temperature of outlet fluid and efficiencies of energy and exergy are more. In general, while the trend of variation of exergy efficacy with impressive parameters is increasing, using the mixers precipitate the efficacy increment. Furthermore, for the case that the trend of variation of exergy efficacy with altering these parameters is reducing, the reducing trend gets slow. Finally, it is realized that using corrugated booster reflectors have a significant effect on collector efficacy, and the highest exergy efficacy was obtained for the 50 degrees corrugations. At Re = 6800, the maximum Nusselt number achieves and it is about 6.03. Finally, using an artificial neural network, the output parameters were navigated with acceptable accuracy. For 76.6% of the data points, the margin of deviation (MOD) was < 1%, and for the rest, the maximum MOD was 2%.
Keywords: Collector; Exergy optimization; Radiation; Forced convection; Corrugated booster reflectors; Photovoltaic cells; ANN